Development of a GC-MS method to determine toxic alcohols and their metabolites in postmortem blood - Grevel, Carl (Department of Pathology, 2025)
The intentional and accidental ingestion of toxic alcohols represents a health care and potential public health concern within South Africa. Household and industrial antifreezes and brake fluids contain ethylene glycol (ETG) and diethylene glycol (DEG), which cause toxicity within humans. Other toxic alcohols such as 1,4-butanediol (1,4-BD) and propylene glycol (PGL) also show toxicity within the human body. Some of these analytes have previously been implicated in cases of fatal poisoning. However, the extent to which toxic alcohols contribute to death in South Africa is yet to be determined, as these are not routinely investigated in forensic toxicological analysis of biological samples. The purpose of this study was to modify and characterise a gas chromatography-mass spectroscopy (GC-MS) method for the quantitative determination of ETG, DEG, 1,4-BD, PGL, and the toxic metabolite of ETG, glycolic acid (GCA), in postmortem whole blood samples at the Forensic Toxicology Unit (FTU) in the Western Cape, South Africa. We describe the alteration of an existing method that examines most of these target analytes among others by Meyer, Weber and Maurer (2011), utilising a lower quantity of N,O-bis-(trimethylsilyl) trifluoroacetamide (BSTFA) and post-mortem whole blood rather than plasma. The method was characterised according to parameters of calibration model, limit of detection, limit of quantification, bias, precision, processed sample stability, and carryover. Linearity was observed for all analytes between 25– 100 µg/mL with preliminary limits of detection at 25 µg/mL. Preliminary limits of quantification were 25 µg/mL for 1,4-BD, and 50 µg/mL for ETG, PGL, GCA and DEG. Recovery was calculated at ~40% for all analytes, and processed sample stability was calculated to be acceptable for up to 72 hours. The developed method was applied to several post-mortem cases of toxic alcohol ingestion at the Observatory Forensic Pathology Institute (OFPI). In conclusion, the method for the determination of toxic alcohols in post-mortem samples was successfully developed and characterised for a government forensic toxicology laboratory in the Western Cape. Future work will include the validation of this method to streamline analytical determination of the morbidity and mortality related to toxic glycols in the Western Cape